2017
DOI: 10.1016/j.alcr.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The transition to adulthood and pathways out of the parental home: A cross-national analysis

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
3
24
0
6
Order By: Relevance
“…United States, United Kingdom, Finland) from analyses using similar methods (Amato et al, 2008;Osgood et al, 2005;Räikkönen et al, 2012;Schoon, 2014), which is surprising in light of the cultural, social and economic differences between these countries. The pathways identified in international comparisons (which included Hungarian data) are also partially consistent with the groups we have found (Lesnard et al, 2016;Schwanitz, 2017). Each of the cited studies found a relatively populous, educated, childless group, independent from parents, which corresponds to our "late family formation after prolonged education" pathway.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…United States, United Kingdom, Finland) from analyses using similar methods (Amato et al, 2008;Osgood et al, 2005;Räikkönen et al, 2012;Schoon, 2014), which is surprising in light of the cultural, social and economic differences between these countries. The pathways identified in international comparisons (which included Hungarian data) are also partially consistent with the groups we have found (Lesnard et al, 2016;Schwanitz, 2017). Each of the cited studies found a relatively populous, educated, childless group, independent from parents, which corresponds to our "late family formation after prolonged education" pathway.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies applying sequence analysis have often made comparisons between youth in different countries and/or different cohorts. Examples being the works of Elzinga and Liefbroer (2007), who compared nineteen, mostly European countries; Lesnard, Cousteaux, Chanvril and Le Hay (2016), who compared twenty; and Schwanitz (2017), who compared eight European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The two paths that are found in most of the studied Western societies describe youth with early or late transitions in most life domains. “Late starters” pathway is characterized by delayed transitions to adult roles, that is, a prolonged life in parental home and slow family formation (Eliason et al, 2015; Osgood et al, 2005; Robette, 2010; Salmela-Aro et al, 2011; Schoon, Chen, Kneale, & Jager, 2012; Schwanitz, 2017). Early transitions characterize a more traditional “early starters” pathway to stable work and family life (e.g., Eliason et al, 2015; Osgood et al, 2005; Robette, 2010; Salmela-Aro et al, 2011; Schoon et al, 2012).…”
Section: Transitions To Adulthood In Modern Western Cultural Contextsmentioning
confidence: 99%
“…Early transitions characterize a more traditional “early starters” pathway to stable work and family life (e.g., Eliason et al, 2015; Osgood et al, 2005; Robette, 2010; Salmela-Aro et al, 2011; Schoon et al, 2012). When it comes to Europe, these two pathways are more commonly followed by youth from less economically developed countries, in particular, Eastern European ones (Schwanitz, 2017).…”
Section: Transitions To Adulthood In Modern Western Cultural Contextsmentioning
confidence: 99%
See 1 more Smart Citation